Exploring critical factors in referral systems at different health‐care levels - Farrukh Jamal (8605026) (2024)
Background A consistent referral system and patient patronage are the primary connections between the three tiers in the healthcare delivery system. Patients were scheduled to visit primary care clinics for the first time. Subsequently, patients are moved to more distinguished healthcare facilities to receive additional care. Objectives This study aims to investigate the reasons behind patients' transfer from primary and secondary care to tertiary care, as well as the critical factors that influence these referrals. Methods This study employs a mixed‐methods approach to explore factors determining referral service provision across primary, secondary, and tertiary healthcare levels. Along with conducting semi‐structured interviews with healthcare professionals, we systematically examined a wealth of retrospective data on 1331 referred patients from 130 health facilities, including patient records, demographics, referral status, and clinical presentation. All statistical analysis was processed in R, and Corel Draw 12 was also used for graphical illustration. Results Healthcare facilities referred most emergencies to several departments, including the cardiac care unit, medical, urology, intensive care unit/emergency, obstetrics and gynaecology, children's, orthopaedic, and psychiatry. The percentage of all cases referred is displayed ward‐by‐ward; the intensive care unit/emergency wards have a high referral ratio of 65.51%, while the obstetrics and gynaecology wards have an 18.40% referral ratio. Conclusion There is a need for increased government investments to strengthen the capacity, human resources, and availability of equipment in primary, secondary, and tertiary public health facilities to deliver quality services in order to reduce the patient referral ratio. Other Information Published in: World Medical & Health Policy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/wmh3.632